Dry deposition, concentration and gas/particle partitioning of atmospheric carbazole - Esen, Fatma; Tasdemir, Yuecel; Cindoruk, S. Siddik (ELSEVIER SCIENCE INC, 2010)
The atmospheric concentrations and dry deposition of carbazole were measured to present the temporal changes, gas/particle partitioning and magnitude of fluxes. Atmospheric samples were collected from July 2004 to May 2005 at four different sites in Bursa, Turkey. The average total (gas and particulate) carbazole concentrations were 7.6 +/- 9.9 ng m(-3) in Gulbahoe (Residential), 1.1 +/- 1.2 ng m(-3) in BUTAL (Traffic), 33 +/- 5.0 ng m(-3) in BOID (industrial), and 1.2 +/- 0.7 ng m(-3) in the Uludag University Campus (UU) (Suburban). Experimental gas/particle partition coefficient (K-P) was determined using the study results and compared with K-P values calculated from octanol-air and soot-air+octanol partitioning models. Total dry deposition fluxes of carbazole were 290 +/- 484 ng m(-2) d(-1) in BUTAL and 72 +/- 67 ng m(-2) d(-1) in the UU Campus. Particulate phase dry deposition velocities were 0.81 +/- 0.78 cm s(-1) and 0.90 +/- 1.53 cm s(-1) for BUTAL and the UU Campus, respectively. On the other hand, gas-phase mass transfer coefficients were calculated to be 0.34 +/- 0.29 cm s(-1) and 026 +/- 0.17 cm s(-1) for BUTAL and the UU Campus, respectively. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Carbazole; Dry deposition flux; Partitioning; Deposition velocity; Bursa; POLYCYCLIC AROMATIC-HYDROCARBONS; POLYCHLORINATED-BIPHENYLS PCBS; SUBURBAN SITE; URBAN SITE; PAHS; AIR; VELOCITIES; GAS; COEFFICIENT; Meteorology & Atmospheric Sciences